Dielectric and electro-optic studies of a ferroelectric liquid crystal dispersed with different sizes of silica nanoparticles. Issue 14 (7th December 2020) - Kaur, Gagandeep; Kumar, Pankaj; Singh, Ashwani Kumar; Jayoti, Divya; Malik, Praveen
ABSTRACT: The impact of the size of silica nanoparticles (SNPs) on the properties of ferroelectric liquid crystals (KCFLC 10R) has been investigated by electro-optical and dielectric techniques. We have found that the doping of silica nanoparticles in the host ferroelectric liquid crystal strongly affects the various properties of doped systems. Doping of silica nanoparticles shows a small decrease in spontaneous polarisation and faster switching time. An improvement in permittivity and conductivity with the temperature at a constant frequency was also noticed after dispersion. This dependence is stronger for large size particles ( ∼ 40 nm) and weaker for small size particles (~12 nm). The Goldstone mode (GM) shifts towards the higher relaxation frequency. These results would be useful to manufacture better optical and electronic devices for display, switching and beam steering applications. Graphical abstract: uf0001